IMPROVING PHYSICS LEARNING OUTCOME THROUGH COOPERATIVE LEARNING MODEL OF GROUP INVESTIGATION TYPE AND STUDENT LEARNING MOTIVATION IN SMAN 1 PESANGGARAN-BANYUWANGI - Erni Wijayanti; Muhammad Firdaus; Hary Sulaksono (STIE Mandala Jember, 2019)
This research aims to determine the effect of GI type cooperative learning model and learning motivation, as well as the influence of interaction model of cooperative learning type GI and motivation to physics learning outcome. The population in this research is the students of class XI IPA SMAN 1 Pesanggaran-Banyuwangi, which consists of two classes of classes that are homogeneous, the control class and experimental class. The data used in this research are primary data collected from pre-test and post-test for learning outcome, and questionnaires for student motivation data. The instrument before it is tested has been tested for its validity and reliability. The statistical test uses two-way Anova analysis method with the help of SPSS computer program. The results showed that (1) there were significant differences between groups of students using cooperative type of GI learning model with conventional learning model on Physics learning Outcome. This conclusion is based on the result of two-way Anova analysis, the value (F Count) 13.491> (F table) 3,13 at significance level (α) 0,05 and P value (Sig.) 0.000 <(α) 0,005. (2) there is a significant difference of influence between high motivated group of students with low motivation toward Physics learning Outcome This conclusion is based on the result of analysis of two path Anova analysis, that is value (F Count) 14,908 <3,13 (F table) on level Significance (α) 0.05 and P value (Sig) 0.000 <(α) 0.05. (3) There is no interaction of GI type cooperative learning model and learning motivation toward student physics learning result at SMAN 1 Pesanggaran. This conclusion is based on two-way Anova analysis test result (F Count) 0,036 <(F Table) 3,13 at significance level (α) 0,05, and P value (Sig) 0,851 <(α) 0,05. From the results of this research teachers are required to always innovate in choosing a model of learning. Due to selection of learning models in accordance with the conditions of learners and schools, it will be able to improve learning outcome. One of the learning models that can improve learning outcome is by using the GI model.